DIGITAL ADAPTATION IN ARABIC LANGUAGE LEARNING; OPPORTUNITIES AND CHALLENGES IN THE ERA OF TECHNOLOGY - Wandana, Nina; Ivlatia, Siti Mahrami; Annashir, Aslam; Nasution, Sahkholid (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
Arabic is a subject in religious schools. As time goes by, the media used for learning Arabic increases in accordance with the times, especially in the digital era now making technology-based media is a common thing. The purpose of this research is to explain how the opportunities and challenges of learning Arabic in the technological era. This research is a qualitative research with the aim to identify and analyze the opportunities and challenges of Arabic language in the technological era. Through literature study, by collecting data from various sources of documentation such as printed books and scientific journal articles. The results of this study indicate that there are many opportunities for learning Arabic in this technological era, namely 1) Creating a more interesting learning process, 2) more innovative learning 3) The creation of learning methods that adjust the material, method, and speed 4) Creating a high learning spirit. While the challenges are 1) inadequate infrastructure, 2) The maturity of an educator, and 3) Data Security.